O gênero conto como estratégia de ensino de leitura e produção textual - OLIVEIRA, Roseli de (2023)
The present article entitled “The Story Genre as a teaching strategy for reading and textual production” had as general objective to develop, in the student, ability of reading and textual production of the tale genre. To achieve this goal, it was necessary understand the characteristics and structure of the short story genre; develop the understanding and interpretation of the short story 'The first kiss', by Clarice Lispector, and develop written production from the study of the short story genre. The work has theoretical-methodological framework Moisés (2000), the National Curriculum Parameters (BRASIL, 1998), Antunes (2003), Bakhtin (2003), Solé (1998) and Dolz, Schneuwly, Noverraz (2004). The work was developed through a didactic sequence with 18 classes focused on reading and producing the short story genre.